2006
DOI: 10.1176/ajp.2006.163.12.2164
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cortisol and Progression of Dementia in Subjects With Alzheimer-Type Dementia

Abstract: Higher HPA activity, as reflected by increased plasma cortisol levels, is associated with more rapid disease progression in subjects with Alzheimer-type dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
158
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 329 publications
(165 citation statements)
references
References 55 publications
5
158
1
1
Order By: Relevance
“…The dysregulation in the negative corticosteroid feedback, as well as increased corticosteroid levels, is reported in AD patients and preclinical mouse models [18]. This is supported by the evidence that increased plasma levels have been reported in the early stages of AD patients [19, 20] and decreased sensitivity to low-dose dexamethasone suppression [6]. Similarly, patients with sporadic AD have increased plasma cortisol levels during the onset and later stages [21-23].…”
Section: Endocrinal Dysregulations In the Ad Pathophysiologymentioning
confidence: 87%
See 1 more Smart Citation
“…The dysregulation in the negative corticosteroid feedback, as well as increased corticosteroid levels, is reported in AD patients and preclinical mouse models [18]. This is supported by the evidence that increased plasma levels have been reported in the early stages of AD patients [19, 20] and decreased sensitivity to low-dose dexamethasone suppression [6]. Similarly, patients with sporadic AD have increased plasma cortisol levels during the onset and later stages [21-23].…”
Section: Endocrinal Dysregulations In the Ad Pathophysiologymentioning
confidence: 87%
“…In this regard, Morgese et al [27] demonstrated that early life dietary deficiency in rats resulted in HPA axis hyperactivity and depression-like behavior, with elevated Aβ levels. Neuroendocrine disorders lead to memory deficit and cognitive dysfunction(s) with a high concentration of glucocorticoids in serum resulting in the extensive loss of neurons in the brain thereby progressing to AD symptoms [20]. Brureau et al [28] suggested that elevated glucocorticoids may be the first consequence of amyloid toxicity in a preclinical rat model of AD.…”
Section: Endocrinal Dysregulations In the Ad Pathophysiologymentioning
confidence: 99%
“…Glucocorticoid (cortisol) levels in AD patients are elevated relative to age-matched controls, and several lines of evidence support a role of stress steroids in Aβ regulation (reviewed in [39]). Although glucocorticoids would appear to be an important target in AD, administration of steroids in human AD trials does not alter cognition (ADCS Prednisone Trial [40]) and results of studies from AD rodent models have been mixed [17, 23, 37, 4146]. …”
Section: Discussionmentioning
confidence: 99%
“…Stress has been increasingly recognized as an external factor that can impact the onset and progression of AD (Dong et al, 2004; Wilson et al 2006; Csernansky et al, 2006; Huang et al, 2010; Alkadhi, 2012). Although the mechanisms involved in the effects of stress on the pathogenesis of AD remain unclear, there is growing evidence that CRF and CRF1 receptors play a critical role in the production and aggregation of both Aβ and tau (Kang et al, 2007; Rissman et al, 2007; Carroll et al, 2011; Rissman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals prone to psychological distress are twice as likely to develop AD (Wilson et al, 2005; Wilson et al, 2006). Elevated plasma cortisol levels, often an indicator of stress, have been reported in patients with AD (Swanwick et al, 1998; Umegaki et al, 2000; Rehman, 2002), and higher plasma cortisol levels were correlated with severity of cognitive decline in AD patients (Csernansky et al, 2006). Considering other elements of the HPA axis, investigators have reported a reduction in corticotropin releasing factor (CRF) immunoreactive cells and increases in the density of postsynaptic CRF receptors in the brain of AD patients (Whitehouse et al, 1987; Pomara et al, 1989; Behan et al, 1995; De Souza, 1995).…”
Section: Introductionmentioning
confidence: 99%